ANALISIS KINERJA MESIN PENGGERAK TRAKTOR PERTANIAN MODEL HST KHS 18 JTDB HASIL PERAKITAN LOKAL DI PT X - Saputra, Rudi; Sunaryo, Muhammad Fitrah (Bina Teknika, 2019)
A tractor drive engine uses a production diesel engine owned by Company X that is intended to be researched on the effect of working hours that have been used for 3 years which will re-test the performance of the engine using a running test machine. Problems are limited to the analysis of the testing process and calculations that occur in the performance of the tractor drive engine. The analysis was carried out using the theory of fuel motor energy conservation to obtain results in accordance with the specifications regarding the calculation of the test results of the tractor drive engine.The analytical method used to process existing data which includes efficiency, power, torque and generated rotation. The results of the analysis and discussion can prove that the ability of the performance of the agricultural tractor driving machine to the working hours of the machine is still feasible to be used in accordance with the existing specifications so that it can be further developed in the form of mass products to meet agricultural needs.